Nigerian Prison Reformation: A Necessity Not A Luxury (Jurnal Pembangunan Sosial, 2017)
This article addresses one of the many issues of Nigerian prisons conditions utilizing helpful equity activity against the conventional criminal equity framework, which puts much accentuation on the awaiting trials and the accused person in the prison facilities and subsequently making prison population to increase. The re-integrative Rehabilitation theory was utilized to support the discussion. Logically, to reestablish equity is to correct offenders and degenerates, and re-set up and revivify repelled connections and breakdown of law and order in society. Rehabilitation is a developing non-caretaker, non-reformatory and humanistic procedure for the treatment not punishment of offenders without recourse to legal battle that often results in remanding one party in prison custody. Considering the encompassing merits of rehabilitation justice, there is an urgent need to officially integrate this alternative to incarceration intervention programme into the Nigerian legal system, as this will go a long way in decongesting the seemingly overpopulated correctional institutions in Nigeria. The rehabilitation/restorative justice facilitators, victims and their families, offenders and their families, and ‘community’ as a sole owner of every individual living in it, collectively strive to restore justice, order, security, property, and core values in Nigeria.